Landscape Planning and Rural Development Key Issues and Options Towards Integration - Rega, Carlo (SpringerBriefs in Geography, 2014)
This book aims to contribute to the current debate on how to integrate rural development policies and landscape planning in rural areas. It highlights the key issues at stake and the possibilities for synergies between landscape planning and policies in light of European development policies, particularly the EU's Rural Development Policy and the Common Agricultural Policy (CAP). Case studies from different rural contexts and landscapes are provided, illustrating tools and options to make the advocated integration operational. Recommendations and guidance to policy making are proposed. The case studies presented cover 1) the use of visual assessment techniques to support landscape planning in rural areas; 2) participative applications of landscape assessment techniques in peri-urban areas; 3) multi-scale approaches to landscape management in Alpine areas; and 4) the application of landscape economic evaluation to foster rural development strategies.